Physicochemical parameters, microbiological quality, and antibacterial activity of honey from the Bucovina region of Romania - Liliana Luca; Daniela Pauliuc; Florin Ursachi; Mircea Oroian (Scientific Reports)
Abstract In this study, the physicochemical properties (electrical conductivity (EC), pH, free acidity, moisture content, DPPH radical scavenging activity, total polyphenols content (TPC), flavonoids content (FC), individual polyphenols, carbohydrates, and organic acids), microbiological quality, and antibacterial activity of honey (raspberry, rosehip, alfalfa, hawthorn, and honeydew honey) from Bucovina were evaluated. Along with melissopalynological analysis, the physicochemical parameters were determined for the honey samples to characterize the samples and to assess their applicability in classifying honey based on its botanical origin. Another objective of the study was the evaluation of the microbiological quality and antibacterial activity of honey samples. The antibacterial activity was examined against the growth of four pathogenic bacterial strains (Staphylococcus aureus ATCC 29213, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, and Salmonella enterica serovar Typhimurium ATCC 14028) by the diffusion test in the agar well and by determining the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). The analyzed honey samples were within the safe limits, except for three samples in which Bacillus cereus was detected and two other samples that had values above the acceptable limit for yeasts. Thus, 40.46% of all honey samples had bactericidal activity that was superior or at least comparable to manuka honey MGO550 against Staphylococcus aureus, 57.69% against Salmonella enterica serovar Typhimurium, 74.15% against Pseudomonas aeruginosa, and 75% against Escherichia coli. Of all types of honey analyzed in this study, honeydew honey had the highest bactericidal activity, followed by polyfloral honey.